Upon a slight rearrangement this problem gets a lot simpler to see.
x^3-x+2x^2-2=0 now factor 1st and 2nd pair of terms...
x(x^2-1)+2(x^2-1)=0
(x+2)(x^2-1)=0 now the second factor is a "difference of square" of the form:
(a^2-b^2) which always factors to (a+b)(a-b), in this case:
(x+2)(x+1)(x-1)=0
So g(x) has three real zero when x={-2, -1, 1}
A the 12 pack box of 1.4 ounce bars
Answer:
C
Step-by-step explanation:
Answer:
(1, 4.5 )
Step-by-step explanation:
The required point is at the midpoint of AB
Use the midpoint formula
Given A(4, 3) and B(- 2, 6 ), then
midpoint = [ 0.5(4 - 2), 0.5(3 + 6) ] = (1, 4.5 )
x = 13
subtract x from both sides of the equation
6 = 2x - x - 7
6 = x - 7
add 7 to both sides
6 + 7 = x ⇒ x = 13
As a check
substitute this value into the equation and if both sides are equal then it is the solution
left side = 13 + 6 = 19
right side = (2 × 13) - 7 = 26 - 7 = 19
hence x = 13 is the solution